Developing drowning prevention strategies for rivers through the use of a modified Delphi process. Issue 3 (30th March 2019) - Peden, Amy E; Franklin, Richard C; Leggat, Peter A
Abstract : Introduction: Internationally, rivers are a leading drowning location, yet little evidence exists evaluating river drowning prevention strategies. This study aims to use expert opinion to identify strategies more likely to be effective. Methods: Using a modified Delphi process, a virtual panel of 30 experts from 12 countries considered, grouped and prioritised strategies for river drowning prevention. Proposed strategies were assessed against known evidence and suitability in high-income countries (HICs) as well as low-income and middle-income countries (LMICs) using expert opinion. The final phase consolidated a list of strategies whose effectiveness was assessed against 10 evidence-based river drowning scenarios. Results: An initial list of 424 prevention strategies was refined to 22. After being assessed against the 10 scenarios, a final list of 13 strategies was derived. Strategies addressed alcohol consumption around rivers, flood mitigation, improving child supervision, learning to swim, increased lifejacket wear and achieving community-wide resuscitation skills. Discussion: While all 13 strategies were assessed as being effective in both LMICs and HICs by at least 60% of the respondents, further work is required to define river drowning at a country level and therefore allow for effective solutions to be developed, particularly in LMICs. No strategy will be effective in isolation and must be implemented alongside policy and behaviour change, public awareness and education. Evaluation should be incorporated as part of any future implementation of strategies. Conclusion: This Delphi process identified 13 drowning prevention strategies for rivers. Further research is required to validate the efficacy of these findings through implementation and evaluation.